Analysis of the Influence of Good Corporate Governance on Earnings Quality in Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) - Monang Tarigan; Harlen Silalahi; Berlin Barus; Dumariani Silalahi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to analyze the influence of Good Corporate Governance (GCG) mechanisms on the earnings quality of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2023 period. Using a quantitative approach and multiple linear regression analysis, this research examines the impact of managerial ownership, institutional ownership, board independence, audit committee, and board size on earnings quality measured by the Modified Jones Model. The sample consists of 60 manufacturing firms selected through purposive sampling based on their disclosure completeness and audited financial reports. The results show that managerial and institutional ownership have a positive and significant effect on earnings quality, indicating that both internal and external ownership structures enhance monitoring and reduce earnings manipulation. Board independence and audit committee activity also contribute positively to earnings reliability, confirming their essential role in strengthening oversight and internal control systems. Furthermore, the simultaneous F-test demonstrates that all GCG mechanisms collectively influence earnings quality, emphasizing the importance of integrated governance in improving financial transparency and credibility. This study concludes that the implementation of GCG principles enhances the trust of investors and stakeholders while promoting sustainable financial reporting practices in Indonesia’s manufacturing sector.